2005
DOI: 10.1021/np0497447
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Synthetic 2,2-Dimethylpyranocoumarins with Antibacterial Activity

Abstract: A new efficient synthetic approach to the natural coumarins 5-hydroxyseselin (5), 5-methoxyseselin (3), and (+/-) cis-grandmarin (9) is described as well as the synthesis of some new derivatives in the 5-methoxyseselin series (10-15). The natural coumarins 7-hydroxyalloxanthyletin (6), alloxanthoxyletin (8), and dipetalolactone (7) have also been obtained as secondary products. The type of fusion of the pyrano ring in all cases has been established by 2D NMR spectroscopy. The compounds have been studied for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(60 citation statements)
references
References 17 publications
(55 reference statements)
0
57
0
Order By: Relevance
“…Coumarin and its derivatives have shown a diverse array of biological activities including antimicrobial [17], chemotherapeutic [18,19], anticoagulant [20] and antiinflammatory [21]. A number of both naturally occurring and synthetic coumarins including aminocoumarins [22,23], hydroxycoumarins [24,25], pyranocoumarins [26], and furanocoumarins [27] have been reported to have significant antimicrobial activity against a wide range of microbes. Following on from our previous work on a series of Ag(I) complexes of coumarin-3-carboxylates, which have proven antimicrobial activity and potential as effective biocides in hygienic coatings, a novel series of Ag(I) complexes of coumarin-4-carboxylates has been synthesised and screened for their antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Coumarin and its derivatives have shown a diverse array of biological activities including antimicrobial [17], chemotherapeutic [18,19], anticoagulant [20] and antiinflammatory [21]. A number of both naturally occurring and synthetic coumarins including aminocoumarins [22,23], hydroxycoumarins [24,25], pyranocoumarins [26], and furanocoumarins [27] have been reported to have significant antimicrobial activity against a wide range of microbes. Following on from our previous work on a series of Ag(I) complexes of coumarin-3-carboxylates, which have proven antimicrobial activity and potential as effective biocides in hygienic coatings, a novel series of Ag(I) complexes of coumarin-4-carboxylates has been synthesised and screened for their antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…2 and Fig. 5 shows a typical ESI-QTOF-MS/MS spectrum of protonated seselin (7). Minor signals were observed at m/z 187.0469 (C 11 H 7 O 3 + ) and 159.0439 (C 10 H 7 O 2 + ).…”
Section: Merazin (5)mentioning
confidence: 99%
“…Pyranocoumarins contain a six-membered ring and can exist in either linear or angular forms. An example of a pyranocoumarin is seselin (7), in which the oxygen at the 7-position is part of a fused six-membered heterocyclic ring system. Another major group is the coumarins that are substituted in the pyrone ring in either position 3 or position 4, such as 3,6-dimethyl-4-hydroxycoumarin (3), also investigated in this paper.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1945, Goth conducted the first antibacterial activity studies of coumarins and found that dicoumarol inhibited the growth of several bacterial strains (Goth, 1945). Melliou et al (2005) found that pyranocoumarin derivatives have a broad spectrum of activity. Dadak & Hodak (1966) suggested that the coumarins with antibacterial activity act selectively against gram positive bacteria.…”
Section: Introductionmentioning
confidence: 99%